(3GdeSFhdjI GdLfGFjI ddMOK (B: s (3OQGSI ebGQfI Hjf GdabI GdESdGei hGdbGfhf GdLfGFi GdhVYi (B/ s - (3LeGd eMeO HQcI YHOGdYGds; (3ahRjI YHOGdSJGQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JfGhd gPG GdHMK GdeSFhdjI GdLfGFjI ddMOK OQGSI ebGQfI Hjf GdabI GdESdGei hGdbGfhf GdhVYi hPdc ai EWGQ NWI Ydi CUhd GdHMK GdYdei hGdJWhQ GdJTQjYi deSFhdjI GdCMOGK GdLfGFjI (B.(3hJfGhd gPG GdHMK GdMOK GdefMQa hGdeYQV ddGfMQGa ai GdabI GdESdGei hGdbGfhf GdhVYi afGbT ajI GdeaGgje GdCSGSjI GdNGUI HGdOQGSI Ke JfGhd HYO Pdc JOQL GdeSFhdjI GdLfGFjI ddCMOGK ai GdabI GdESdGei hGdbGfhf GdebGQf afGbT ajg CMcGe eQMdJi GfYOGe GdeSFhdjI heQMdI GdeSFhdjI GdLfGFjI GdfGbUI ai cd ef GdabI GdESdGei hGdbGfhf GdebGQfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2009s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B326-338s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdabI GdESdGei s; (3GdbGfhf GdLfGFi GdhVYi s; (3GdeSFhdjI GdLfGFjI ddMOKs; (3GdMOK GdefMQas; (3GdMOK GdeYQV ddGfMQas; (3eYGedI GdCMOGKs; (3GdJOGHjQ GdJgPjHjIs; (3GdeYGedI GdYbGHjI ddCMOGKs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs